INTEGRASI DI KAWASAN STRATEGIS CAGAR BUDAYA BENTENG MALBOROUGH, BENGKULU - Abdul Hamid Hakim (Jurnal Tekno Global, 2016)
Strategic Area Heritage Fort Malborough merupak one area that became a tourist destination which is very important in the city of Bengkulu. Within this area consists of several areas, namely Region Thomas Parr, New Market Region Koto, Region Chinatown, Fort Malborough Region and Region Tapak Padri. As the unity of a strategic area in the context of tourism and have relevance of the historical development of the city of Bengkulu, should the region - the region can provide mutual support to each other. But the current conditions, the only area of Fort Malborough and Region Tapak Padri is well developed, while the area - other areas showed the opposite. Therefore it is necessary to think of ways to Strategic Region Heritage Fort Malborough can be integrated with each other so as to provide alternative travel options and positive impact on the progress of development of the city.In this study, using a mixture of deductive deductive qualitative and quantitative. The process of the study discusses the characteristics to determine the basic character formed in the region by using methods other research deductive qualitative and discuss the quantity of integration contained in Strategic Area Heritage Fort Malborough research method deductive quantitative results of the characteristics and quantity of such integration is then processed to get a conclusion the research is a concept - a concept that is suitable to be applied to integrate Strategic Area Heritage Fort Malborough. The results of this research is a concept - a concept that can be applied in order to integrate the region - an area within the strategic areas of cultural heritage fort malborough.Keywords : Characteristics, Integration Region